2021
DOI: 10.1016/j.compbiomed.2021.104570
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel systems biology analysis of lung transcriptomics data identifies key miRNAs and potential miRNA target genes for SARS-CoV-2 infection

Abstract: Background The spread of a novel severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) has affected both the public health and the global economy. The current study was aimed at analysing the genetic sequence of this highly contagious corona virus from an evolutionary perspective, comparing the genetic variation features of different geographic strains, and identifying the key miRNAs as well as their gene targets from the transcriptome data of viral infected lung tissues. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 71 publications
(69 reference statements)
0
37
0
Order By: Relevance
“…Activation of MYC has been observed in IAV infection [112], as well as proposed to target deregulated genes in SARS-CoV-2 infected cells [81]. Analysis of SARS-CoV-2 infected lung transcriptomics data identifies miRNAs that could target MYC indicating a possible role of MYC in the pathogenesis of COVID-19 [141]. Hyperactivation of the NFκB pathway involves the survival, activation, and differentiation of innate immune cells inflammatory T cells and has been implicated in the pathogenesis of the severe/critical COVID-19 patients [77].…”
Section: Mechanism Of Deregulation Of Lncrna and Pcgmentioning
confidence: 96%
“…Activation of MYC has been observed in IAV infection [112], as well as proposed to target deregulated genes in SARS-CoV-2 infected cells [81]. Analysis of SARS-CoV-2 infected lung transcriptomics data identifies miRNAs that could target MYC indicating a possible role of MYC in the pathogenesis of COVID-19 [141]. Hyperactivation of the NFκB pathway involves the survival, activation, and differentiation of innate immune cells inflammatory T cells and has been implicated in the pathogenesis of the severe/critical COVID-19 patients [77].…”
Section: Mechanism Of Deregulation Of Lncrna and Pcgmentioning
confidence: 96%
“…Four key miRNAs (hsa-miR-342-5p, hsa-miR-432-5p, hsa-miR-98-5p, and hsa-miR-17-5p) are believed to be involved in antiviral SARS-CoV-2 gene silencing (ORF1ab) [ 72 ]. For three miRNA (hsa-miR-17-5p, hsa-miR-20b-5p, and hsa-miR-323a-5p), there is experimental evidence of having antiviral roles during infections against SARS-CoV-1 and SARS-CoV-2 ( Table 3 ) [ 73 ].…”
Section: Changes In Mrna Expression—mirna ‘’Silencing’’ Interferencementioning
confidence: 99%
“…Published data show that virus RNA highly interacts with human miRNAs to change the expression of important defense molecules [ 29 , 72 , 73 ]. Our analysis showed that numerous human miRNA may form duplexes with different coding and non-coding regions of viral RNA.…”
Section: Changes In Mrna Expression—mirna ‘’Silencing’’ Interferencementioning
confidence: 99%
“…However, differences in the type of clinical samples, array platforms, and statistical approaches used, created a discordance in interpreting massive transcriptomics data. Advances in statistical modeling and bioinformatics approaches have accelerated the identification of disease-centric genes by employing gene networking methods based on graph topological parameters for many infectious diseases (7,8). Moreover, the new bioinformatic methods like estimating relative subsets of RNA transcripts (CIBERSORT), Tumor Immune Estimation Resource (TIMER), and Estimating the Proportions of Immune and Cancer cells (EPIC) are developed to characterize immune cell composition using large-scale gene expression data (9,10).…”
Section: Introductionmentioning
confidence: 99%